Shifting of the Da Rang River Mouth and Its Relationship with Adjacent Sandy Coast - Nguyen, Trong Hiep (2020)
Phenomenon of accretion and erosion at the Da Rang River mouth has been observed to be severe for a long term. Based on the satellite images- Landsat images, the long-term evolution of this area from 1988 until now has been raised to discuss. The shoreline variation in the river mouth has happened in an unpredictable way; indeed, the adjacent areas in which at both sides of the river mouth have much changeable while the areas far from the river mouth have been seen to have minor change. This study applies even-odd method to analyze the variation of the shoreline at the Da Rang River mouth. The formation of both sides of the river mouth varied consecutively in the period from 1988- 2015. The onshore/offshore retreat and advance of both sides represents the even portion while the odd portion represents the longshore sediment effects.